Документи Державного архіву Волинської області як джерело до вивчення історії єврейської громади Олики (кінець ХVІІІ – 30-ті рр. ХХ ст.) - Надольська, Валентина Василівна; Nadolska, Valentyna (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проаналізовано документи Державного архіву Волинської області, які характеризують соціально-економічні, правові, релігійні, культурні аспекти історії євреїв Олики кінця ХVІІІ – 30-х рр. XX ст. Різноманітні за змістом і методами складання, під час аналітичного їх вивчення вони можуть бути використані для дослідження минулого єврейської громади містечка. The documents of the State Archives of Volhyniaregion that characterize the social, economic, legal, religious, and cultural aspects of the history of Olyka’s Jews end ХVІІІ– 30’s XX century in article are analyzed. The documents of organizations and institutions operating in the territory of the Volhyniaprovince, and since 1919 – the VolhyniaVoivodeship, have deposited in the seven archival collections. They are diverse in content and methods of compilation. The collections 486 «Olyka City Hall» (1799–1861) and 140 «Olyka Station of the State Police» (1920–1935) are the most informative for the researchers. These documents can be used for study the life of the Jewish community in the city, the history of Olyka as a whole in the analytical study of them.
The Documents of the State Archives of Volhynia Region as a Source for Studying the History of the Jewish Community of Olyka (the End of the XVIII - 30’s of XX Century)
Keywords: Державний архів Волинської області; євреї; Олика; Волинська губернія; Волинське воєводство; архівний фонд; State Archives of Volhynia Region; Jews; Olyka; Volhynia province; Volhynia Voivodeship; archival collections